PENGEMBANGAN KURIKULUM MUATAN LOKAL KEAGAMAAN ISLAM DALAM MEMBENTUK BUDAYA RELIGIUS DI SEKOLAH - Lamuhtadun, Lamuhtadun (STAI Ma'had Aly Al-Hikam Malang, 2023)
Abstract:This study discusses the design from progressness of local religious content in shaping religious culture at SDN Perak 2 Perak Jombang. This study use qualitative approach. The result of research that has been done regarding the design of the curriculum of local religious content in shaping religious culture at SDN Perak 2 Jombang, show that the implementation of local religious content at SDN Perak 2 Perak Jombang has been going on for 3 years. The material that teaches in local content is more about material that hones the religious skills of students. The teaching materials include prayer, reading and writing of al-Qur'an, worship and invocation, and memorizing letters. As for ordering religious culture SDN Perak 2 Perak through several ways of making school policies in the form of religious regulations and programs, and maximizing the function of religious symbols. The design of local religious content development carried out by SDN Perak 2 in shaping religious culture in schools is realized in an application program. This program is the result of extracurricular development in the local religious content curriculum. In addition, the teacher also develops learning outcomes or learning outcomes of local religious content.